Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No.2, 2018, „Application of a Priori and a Posteriori Estimate on Risk Assessment“, pp. 56-61. The proper name of third author should be as follows: Witalis Pellowski. - Sivakova, Lenka; Zubkova, Anna; Pellowski, Witalis (Communications - Scientific letters of the University of Zilina, 2018)
Errata: Communications – Scientific Letters of the University of Zilina, Vol. 20, No.2, 2018, „Application of a Priori and a Posteriori Estimate on Risk Assessment“, pp. 56-61. The proper name of third author should be as follows: Witalis Pellowski.